Stochastic analysis and one minimization problem - Dorogovtsev, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We consider the problem of finding the form of a functional of an infinite-dimensional argument for which a certain given expression takes the minimum value for a fixed value of the parameter. The equation obtained for an unknown functional resembles equations with extended stochastic integral.